2013
DOI: 10.1371/journal.pone.0061928
|View full text |Cite|
|
Sign up to set email alerts
|

Metagenomic Analysis of a Tropical Composting Operation at the São Paulo Zoo Park Reveals Diversity of Biomass Degradation Functions and Organisms

Abstract: Composting operations are a rich source for prospection of biomass degradation enzymes. We have analyzed the microbiomes of two composting samples collected in a facility inside the São Paulo Zoo Park, in Brazil. All organic waste produced in the park is processed in this facility, at a rate of four tons/day. Total DNA was extracted and sequenced with Roche/454 technology, generating about 3 million reads per sample. To our knowledge this work is the first report of a composting whole-microbial community using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
77
1
9

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 105 publications
(92 citation statements)
references
References 88 publications
(114 reference statements)
1
77
1
9
Order By: Relevance
“…Both consortia showed presence of phylotypes from the phylum Proteobacteria whose members are known for metabolic diversity48. Members of Bacteroidetes and Actinobacteria present in both communities have been linked to degradation of complex polymers in compost16 and have been reported in composting piles previously4950. Interestingly, MM community was enriched in phylotypes including known and characterized genera such as Cellulomonas, Paenibacillus and Cellvibrio .…”
Section: Discussionmentioning
confidence: 91%
“…Both consortia showed presence of phylotypes from the phylum Proteobacteria whose members are known for metabolic diversity48. Members of Bacteroidetes and Actinobacteria present in both communities have been linked to degradation of complex polymers in compost16 and have been reported in composting piles previously4950. Interestingly, MM community was enriched in phylotypes including known and characterized genera such as Cellulomonas, Paenibacillus and Cellvibrio .…”
Section: Discussionmentioning
confidence: 91%
“…degraded cellulose under the thermophilic and anoxic conditions of a composting pile, especially in the initial stage of the composting process. Martins et al (2013) reported that Bacillales in compost could degrade cellulose and solubilize lignin and colonize substrates under conditions of low nutrient availability. Li et al (2013) showed that some Bacillus spp.…”
Section: Daysmentioning
confidence: 99%
“…The bacterial populations of the compost were studied using a metagenomic approach (Martins et al, 2013). This work showed high bacterial diversity in compost that can fully account for the observed biomass degradation.…”
Section: Description Of Study Sitementioning
confidence: 99%
“…Martins et al (2013), in their study of the microbial diversity of the organic compost used in the vegetable garden of the FPZSP, found a low relative abundance of organisms belonging to the family Enterobacteriaceae. However, we cannot determine whether this microbial contamination occurred through leaching from the vegetable garden because there are other factors that could also explain the observed bacteria, such as the presence of wild animals near the site.…”
Section: Microbiological Parametersmentioning
confidence: 99%